Buso Renkin. Vol. 1, New life - Watsuki, Nobuhiro (Viz Media, 2006)
After high school student Kazuki Muto rescues Tokiko from a monster that eats human flesh, he learns there is only one thing that can annihilate these flesh-eating monsters-- a buso renkin. Now, his heart has been transformed into a buso renkin, and the fight is on.